1995
DOI: 10.1016/0957-4166(95)00237-j
|View full text |Cite
|
Sign up to set email alerts
|

Thiol and disulfide derivatives of ephedra alkaloids 2: A mechanistic study of their effect on the addition of diethyl zinc to benzaldehyde

Abstract: Take-down policy If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
2

Year Published

1997
1997
2008
2008

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(31 citation statements)
references
References 11 publications
0
29
0
2
Order By: Relevance
“…Subsequently, Noyori and co-workers [22,24] Bolm et al, [25] and Kellogg and co-workers [26] reported the presence of an NLE in this class of reactions. The formation of stable and catalytically inactive heterochiral dimers 2 was suggested as a possible explanation for the occurrence of the NLE.…”
Section: Addition Of Dialkylzinc Reagents To Aldehydesmentioning
confidence: 96%
“…Subsequently, Noyori and co-workers [22,24] Bolm et al, [25] and Kellogg and co-workers [26] reported the presence of an NLE in this class of reactions. The formation of stable and catalytically inactive heterochiral dimers 2 was suggested as a possible explanation for the occurrence of the NLE.…”
Section: Addition Of Dialkylzinc Reagents To Aldehydesmentioning
confidence: 96%
“…1,75,76 To elucidate the mechanistic aspects, we assumed that the disulfide linkage is cleaved by nucleophilic attack of diethylzinc, resulting in the thiolate 5 and the thioether 6 (Scheme 2), according to the results reported by Kellogg 35 and Wirth. 30 Aiming to identify the catalytically active species, we prepared the compound 6 via 2a ring-opening reaction by attack of EtSSEt/NaBH 4 77 as shown in Scheme 3.…”
Section: Resultsmentioning
confidence: 99%
“…25 In the last few years, a significant improvement in enantioselectivity has been observed by the use of amino sulfur or selenium moieties as catalysts for the enantioselective addition of diethylzinc to aldehydes. [26][27][28][29][30][31][32] Sulfur containing ligands 33 like b-amino thiols and b-amino disulfides derivatives from ephedrine, [34][35][36] norephedrine, [37][38][39] (S)-proline, [40][41][42] (S)-phenylglycine, 43 (S)-valine, 44,45 (R)-cysteine, 5,46-50 (R)-cystine, 51 and others [52][53][54][55][56][57][58] have gained more and more interest as catalysts in this stereoselective reaction. In a similar way, chiral amino diselenides have been efficiently used as catalysts for this addition, [28][29][30][31][32] but due to the most difficult accessibility of these compounds, only a few number of reports can be found in literature.…”
Section: Introductionmentioning
confidence: 99%
“…We assumed that the diselenide linkage is cleaved by nucleophilic attack of diethylzinc, resulting in zinc selenolate 33a and selenoether 33b, according to the results reported by Kellogg [27] and Wirth [15]. We believe that the active catalyst of the reaction is selenolate 33a, since in an additional experiment selenoether 33b did not catalyze the alkylation of benzaldehyde.…”
Section: Diethylzinc Additionmentioning
confidence: 92%